Enhanced heterogeneous photo-Fenton-like degradation of tetracycline over CuFeO2/biochar catalyst through accelerating electron transfer under visible light. (1st May 2021) - Xin, Shuaishuai; Ma, Bingrui; Liu, Guocheng; Ma, Xiaoming; Zhang, Chunlei; Ma, Xiaohan; Gao, Mengchun; Xin, Yanjun
Abstract: The visible-light induced heterogeneous photo-Fenton-like (HPF-like) process is regarded as a promising technique for organic pollutants degradation due to its efficient utilization of solar energy and high H2 O2 activation activity. This study prepared the CuFeO2 /biochar catalysts via hydrothermal technique at no extra reductant and systematically investigated their band structure and photoelectric properties. The dispersed distribution of CuFeO2 particles in CuFeO2 /biochar composites narrowed bandgap of CuFeO2 and promoted electron transport of CuFeO2 . Compared with CuFeO2, the CuFeO2 /biochar containing 1.0 g biochar in the preparation (CuFeO2 /biochar-1.0) possessed higher carrier density and longer photoelectron lifetime, which is beneficial to higher catalytic performance. The apparent rate constant for tetracycline as target pollutant degradation by CuFeO2 /biochar-1.0 was 2.0 times higher than that by CuFeO2 . The acquired optimum conditions for tetracycline degradation were 220 mg L −1 CuFeO2 /BC-1.0, 22 mM H2 O2 and pH 6.4 using response surface methodology. The quenching experiments and ESR analysis revealed that OH was the predominant active species, and photoelectron and O2 − were auxiliary species. The photoelectron could promote in-situ recycling of Cu 2+ to Cu + and Fe 3+ to Fe 2+, which significantly improved H2 O2 activation by CuFeO2 . The possible pathway of tetracycline was proposed according to intermediates identified by HPLC/MS. The toxicity analysis demonstrated that the overall toxicity of the identified intermediates was reduced in HPF-like system. Graphical abstract: Image 1 Highlights: Biochar narrowed bandgap and facilitated interface electron transfer of CuFeO2 . Biochar extended photoelectron lifetime and enhanced carrier density of CuFeO2 . Efficient degradation of tetracycline by CuFeO2 /biochar in HPF-like system. OH, e − and O2 − rather than h + played a role in tetracycline degradation. The photoelectron greatly promoted in-situ recycling of Cu 2+ to Cu + and Fe 3+ to Fe 2+ .